Novos problemas da iconografia de D. Duarte - Flor, Pedro (2021)
This article reviews the problems on the iconography of D. Duarte, following other studies recently developed under the subject of the art of portrait in Portugal. From new elements, text deepens the issues related to the image of the King and its heraldry, considering the historical and artistic context of the first half of the fifteenth century in Portugal, in particular in painting.